2009
DOI: 10.1677/joe-08-0460
|View full text |Cite
|
Sign up to set email alerts
|

Activins regulate 17β-hydroxysteroid dehydrogenase type I transcription in murine gonadotrope cells

Abstract: Activins are pleiotropic members of the TGFb superfamily and were initially characterized based on their abilities to stimulate FSH synthesis and secretion by gonadotrope cells of the anterior pituitary gland. Here, we identified the gene encoding the steroidogenic enzyme, 17b-hydroxysteroid dehydrogenase type I (17b-HSD1; Hsd17b1), as an activinresponsive gene in immortalized gonadotrope cells, LbT2. 17b-HSD1 catalyzes the conversion of estrone to the more active 17b-estradiol, and activin A stimulated an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Only a few genes were previously known to be associated with activin A signaling. For instance, activin A regulates transcription of sex hormone synthesizing enzymes of the hydroxysteroid dehydrogenase (Hsd17) family . Link et al uncovered that prostate transmembrane protein, androgen induced 1 ( Pmepa1 ) is a novel and direct target gene of activin A‐mediated Smad2/3 signaling in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few genes were previously known to be associated with activin A signaling. For instance, activin A regulates transcription of sex hormone synthesizing enzymes of the hydroxysteroid dehydrogenase (Hsd17) family . Link et al uncovered that prostate transmembrane protein, androgen induced 1 ( Pmepa1 ) is a novel and direct target gene of activin A‐mediated Smad2/3 signaling in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, activin A regulates transcription of sex hormone synthesizing enzymes of the hydroxysteroid dehydrogenase (Hsd17) family. (28) Link et al (29) uncovered that prostate transmembrane protein, androgen induced 1 (Pmepa1) is a novel and direct target gene of activin A-mediated Smad2/3 signaling in the brain. Moreover, we found that activin A regulates expression of genes that are known to be involved in TGF-b signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse GCs, the lipotoxicity, which is closely related to obesity, significantly decreases the mRNA expression of HSD17B1 (Hua et al., 2020), and it is suggested that Farnesoid X receptor regulates the mRNA expression of HSD17B1 and thus regulates the synthesis of steroid hormone (Takae et al., 2019). In murine gonadotrope cells, HSD17B1 has been suggested as an activin‐responsive gene (Bak et al., 2009). Moreover, the methoxychlor is a known endocrine disruptor that affects adult rodent females by causing reduced fertility, and Basavarajappa et al have found that the methoxychlor decreases the sex steroid hormone levels by inhibiting the expression of HSD17B1 in mouse (Basavarajappa et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The results did not indicate, however, whether these effects were gene specific or reflected a generalized antagonism of activinlike signaling. We therefore examined the effects of TSA on a second activin A-responsive gene in LβT2 cells, 17β-hydroxysteroid dehydrogenase type I (Hsd17b1) (Bak et al 2009). Similar to the case with Fshb, TSA greatly attenuated basal and activin A-induced Hsd17b1 expression ( Fig.…”
Section: Tsa Impairs Expression Of Another Activin Target Hsd17b1mentioning
confidence: 99%